PENGARUH PERENCANAAN PEMBELAJARAN TERHADAP PENINGKATAN KUALITAS DAN MUTU PENDIDIK DALAM KEGIATAN MENGAJAR DI SDN BANJAR 1 - Nurhasanah, Ana; Adya Pribadi, Reksa; Renna Apriliana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
This study aims to determine the application of learning planning at SDN Banjar 1. To find out the quality of teachers in the process of teaching activities. And to find out the effect of learning planning on improving the quality and quality of educators in teaching activities at SDN Banjar 1. The research population is all educators at SDN Banjar 1, totaling 50 people. The results of the study illustrate that the professionalism of teachers at SDN Banjar 1 in teaching is classified as very good, competent and has achieved learning objectives as expected and in accordance with what has been previously determined.